Voriconazole treatment of pulmonary mycosis caused by Chrysosporium zonatum after treatment for pulmonary tuberculosis. Issue 6 (7th May 2021) - Matsuzaki, Takuya; Kasai, Hajime; Ikeda, Hideki; Tajiri, Yuki; Suzuki, Kenichi; Watanabe, Akira; Kamei, Katsuhiko; Urushibara, Takashi
Abstract: Chrysosporium zonatum is a soil‐dwelling fungus that rarely causes pulmonary infections, and a small number of cases have been reported to date. A 74‐year‐old man, who had previously been treated for tuberculosis, presented with symptoms of low‐grade fever, anorexia, cough, and bloody sputum. Chest computed tomography (CT) showed a thick‐walled cavitary lesion in the right upper lobe, in which there was a suspected mycotic mass. Initially, the patient was suspected to have chronic aspergillosis due to positive serum anti‐ Aspergillus antibodies. However, bronchoscopic culture revealed the growth of C. zonatum . Symptoms and imaging findings improved with administration of voriconazole for 18 months. Infection by C. zonatum is very rare and is difficult to differentiate from aspergillosis by clinical features. Clinicians should be aware of the possibility of coinfection with C. zonatum and Aspergillus sp. Voriconazole may be an effective treatment option. Abstract : We present a case of pulmonary mycosis caused by Chrysosporium zonatum after the completion of treatment for pulmonary tuberculosis.